CRISIS ALIMENTARIA Y DESAFÍOS DE LA SEGURIDAD ALIMENTARIA EN CENTROAMÉRICA - Masís Morales, German (2011)
Resumen La crisis mundial de alimentos puso en evidencia la vulnerabilidad de los sistemas alimenticios, demostrando que el impacto más profundo se produce en los países con una mayor dependencia en la importación de alimentos y acompañados de mayores niveles de pobreza. En la región centroamericana, la crisis podría provocar un incremento del costo de la canasta básica alimentaria, un menor acceso a los alimentos, un aumento en la pobreza y en la inseguridad alimentaria y nutricional de la población más vulnerable. Abstract The international food crisis showed the vulnerability of the food supply system. The crisis exposed that the deepest shocks were produced in the countries with the major dependency in imports and highest levels of poverty.   In the upcoming moths, the crisis could provoke an increase in the cost of the alimentary basic basket, a decrease in food access and an enlargement of poverty levels for the countries in Central America. In addition, the weakness on the sovereignty in the alimentary and nutritional security will provoke a major vulnerability in the population with the lowest income.